DIGITAL TRANSFORMATION IN CIVIL CONSTRUCTION: A PROPOSAL FOR THE IMPLEMENTATION OF CONSTRUCTION 4.0 IN SMALL COMPANIES - de Souza, Berg Francisco Alves (Seven Editora, 2026)
This study investigates the transition of the construction industry to the Construction 4.0 paradigm, focusing on overcoming productivity stagnation and the sector’s technological slowdown. The global scenario, driven by the Fourth Industrial Revolution, requires the integration of technologies such as BIM, drones, the Internet of Things, and cloud computing. However, the literature indicates that implementation is challenging, especially for small companies in developing countries, due to high costs, cultural resistance, and the lack of clear roadmaps. The case study conducted in a small construction company in Pernambuco highlights real issues, such as failures in façade inspection and critical incompatibilities between decentralized projects. To address these bottlenecks, an eleven-step methodology is proposed, using Revit software for BIM coordination, the OnSafety platform for digital occupational safety management, and the strategic use of drones for technical monitoring. The results demonstrate that digitalization is feasible and essential for small organizations, leading to greater operational efficiency, error reduction, and increased competitiveness in the regional market.